One new genus and species of Typhlocybinae (Hemiptera: Cicadellidae) from Southwest China - Yuan, Xiao-Wei; Song, Yue-Hua (Zootaxa, 2019)
A new genus, Paraahimia gen. n., and a new species, P. luodianensis sp. n. from Guizhou Province in Southwest China of the subfamily Typhlocybinae are described and illustrated.